2015
DOI: 10.1186/s13104-015-1235-4
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer-associated gene polymorphisms in a nation-wide cohort of p16-Leiden germline mutation carriers; a case–control study

Abstract: BackgroundThe p16-Leiden founder mutation in the CDKN2A gene is the most common cause of Familial Atypical Multiple Mole Melanoma (FAMMM) syndrome in the Netherlands. Individuals with this mutation are at increased risk for developing melanoma of the skin, as well as pancreatic cancer. However, there is a notable interfamilial variability in the occurrence of pancreatic cancer among p16-Leiden families. We aimed to test whether previously identified genetic risk factors for pancreatic cancer modify the risk fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Most pancreatic surveillance programmes lower the age at which surveillance is initiated for individuals with a first-degree relative with young-onset pancreatic cancer (age <50) 49. For mutation carriers, with a deleterious germline variant, the recommended age to initiate surveillance is generally age 50 ( BRCA2, ATM, PALB2 ), though some groups would start surveillance at age 45 and earlier still for the higher-risk genes; surveillance from age 40 is recommended for CDKN2A mutation carriers; 16% of p16-Leiden mutation carriers with pancreatic cancer were diagnosed at age <4550 and at age 30–40 for those with Peutz-Jegher syndrome 3. When to initiate pancreatic surveillance for these mutation carriers did not reach consensus (online supplementary table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Most pancreatic surveillance programmes lower the age at which surveillance is initiated for individuals with a first-degree relative with young-onset pancreatic cancer (age <50) 49. For mutation carriers, with a deleterious germline variant, the recommended age to initiate surveillance is generally age 50 ( BRCA2, ATM, PALB2 ), though some groups would start surveillance at age 45 and earlier still for the higher-risk genes; surveillance from age 40 is recommended for CDKN2A mutation carriers; 16% of p16-Leiden mutation carriers with pancreatic cancer were diagnosed at age <4550 and at age 30–40 for those with Peutz-Jegher syndrome 3. When to initiate pancreatic surveillance for these mutation carriers did not reach consensus (online supplementary table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, cases of melanoma were p16-Leiden carriers who were diagnosed with cutaneous (multiple) melanoma. Detailed medical record data on the study population has been reported previously [12]. Approval of this study was obtained from the ethics committee of Leiden University Medical Center (LUMC #P14.148) [12].…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to identify genetic factors that modulate the risk of pancreatic cancer in p16-Leiden carriers, Potjer et al analyzed seven SNPs associated with PC risk in the general population in this cohort of carriers and found no significant association [12]. Recently a risk variant, rs36115365-C, was identified to be significantly correlated with PC risk in the European population [13].…”
Section: Introductionmentioning
confidence: 99%
“…51 Several studies have shown that PARK2 is also a putative tumor suppressor gene, harboring inactivating mutations in many cancer types including renal cell carcinoma, glioblastoma, and colon, lung, and pancreatic cancers. 53,54 A recent study showed that germline inactivating PARK2 mutations are more frequent in CMM cases than in CMM-free controls (OR 5 3.95, 95% CI 5 1. 53,54 A recent study showed that germline inactivating PARK2 mutations are more frequent in CMM cases than in CMM-free controls (OR 5 3.95, 95% CI 5 1.…”
Section: Park2 (Parkin)mentioning
confidence: 99%
“…42,43,52 Interestingly, pancreatic cancer and nervous system tumors are associated with inherited predisposition to CMM. 53,54 A recent study showed that germline inactivating PARK2 mutations are more frequent in CMM cases than in CMM-free controls (OR 5 3.95, 95% CI 5 1. 34-15.75).…”
Section: Park2 (Parkin)mentioning
confidence: 99%